Welcome and opening remarks: Summary Paper from the International Conference on Sustainable Food Security For All By 2020 - Pinstrup-Andersen, Per (International Food Policy Research Institute, 2001)
The Director-General of IFPRI sets the stage for the conference by pointing to the various important goals, including cooperating to create an environment in which people can escape food insecurity and malnutrition in a manner compatible with sustainable management of natural resources. He calls for a new policy agenda in which the solution of food and nutrition problems are given high priority by governments everywhere.